Criminal Policy of Imposing Community Service for the Crime of Absence Without Leave Committed by the Military - Tetelepta, James Chris Deweighat; Hadi, Agustinus Purnomo; Maryani, Ani (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Community service is one of the main punishments as a sub-system in the imposition of punishment in the sanction system in the Criminal Code. Currently, the sanction system in the Criminal Code and the crimes that occur are interesting to discuss and analyze.Purposes of the Research: Community service is one of the main punishments as a sub-system in the imposition of punishment in the sanction system in the Criminal Code. Currently, the sanctions in the Criminal Code and the crimes that occur are interesting to discuss and analyze. From this, the question is whether the imposition of community service can be applied to military crimes that occur in the Criminal Code, and how the future criminal policy will be for the renewal of military law.Methods of the Research: Normative legal approach method, namely by legal research conducted by examining library materials or secondary data periodically (in addition to the existence of sociological or empirical legal research which mainly examines primary data) by looking at the provisions of existing laws and regulations, through literature review.Results Main Findings of the Research: The legal basis for imposing Social Work sentences in Indonesia is regulated in National Law Number 1 of 2023 concerning the Criminal Code, Article 65, so it is necessary to reform criminal law, especially military criminal law because the purpose of punishment for the military is not only retribution but also guidance and prevention because if the perpetrator of the crime is a military person, it can have a very broad impact both for military interests and public interests.